NURSES’ KNOWLEDGE, ATTITUDE AND PRACTICES OF EMERGENCY CONTRACEPTIVE PROVISION TO CLIENTS IN OGUN STATE, NIGERIA (2014)
Emergency Contraceptives (ECs) are highly effective for the prevention of unwanted pregnancy for up to 72hrs after unprotected sexual intercourse. Timely provision of emergency contraceptives services to clients by nurses can play a vital role in reducing the rate of unplanned pregnancies, abortion and maternal mortality. In Nigeria, there is limited information on competence of nurses on provision of EC services. This study was designed to determine nurses’ knowledge, attitudes and practices of E.C. provision to clients in Ogun State, Nigeria. Using multi-stage sampling technique, from a total of 3,073 nurses in Ogun State, 369 nurses were selected, out of which 99 nurses were working in 58 Primary Health Care (PHC) centres, 154 in 8 Secondary Health Care (SHC) institutions and 116 in one Tertiary Health Care (THC) facility in the State. A semi-structured questionnaire which included a 17-point knowledge, 4-point attitudinal and 3-point practice scales was used for data collection. Respondents who scored ≥ 8.5 points in the knowledge scale were considered to have good knowledge, respondents who scored ≥ 2.5 points in the attitudinal scale showed positive attitude while respondents who scored ≥ 1.5 points in the practice scale showed good practice. Data analysis was conducted using descriptive statistics, ANOVA and Chi- square. Most respondents (95.4%) were females, 72.9% were married while 21.7% were single. Majority (79.6%) had heard of ECs, out of which 17.7% were working in THCs, 37.8% in SHCs and 24.0% in PHCs. Most respondents (94.7%) were aware that EC could prevent pregnancy (20.9% in THCs, 49.3% in SHCs and 24.4% in PHCs). About 19% of respondents stated correctly the dosage and time of administration of an emergency contraceptive. Respondents’ mean knowledge score of ECs was 10.7 ± 5.2. Mean knowledge scores by type of facility were 11.8 ± 4.0 (PHCs), 10.3 ± 5.6 (SHCs) and 10.2 ± 5.4 (THCs). Few respondents, 13.9% from THCs, 33.3% from SHCs and 19.8% from PHCs were of the opinion that health facilities owned by religious organisations should also provide ECs. Some respondents, 6.5% from THCs, 16.2% from SHCs and 12.9% from PHCs, had ever administered ECs and their mean practice score was 13.6 ± 2.9 while the score for those who had never done so was 11.5 ± 3.9. About 7.0% of respondents from THCs, 16.8% from SHCs and 10.6% from PHCs had good knowledge with no significant difference (P<0.05). About 10% of respondents from THCs, 27.0% from SHCs and 12.1% from PHCs had positive attitude with no significant difference (P<0.05). About 6.3% of respondents from THCs, 13.2% from SHCs and 11.9% from PHCs had good practice of provision of EC with no significant difference (P<0.05). Respondents’ knowledge of the mechanism of action of emergency contraceptives was high but their awareness of the dosage and time of administration was poor. In-service training on emergency contraceptives is needed to increase the knowledge of nurses and also to correct their attitudes.